TANTANGAN AUDIT DALAM ERA INFLASI DAN FLUKTUASI NILAI TUKAR PADA PERUSAHAAN MULTINASIONAL - Windya, Yemima Eka Christi; Wila, Syacita Sheril Putri; Tameno, Minshy Leanora (Universitas Nusa Cendana, 2025)
Auditing in the context of inflation and exchange rate fluctuations faces significant challenges. High inflation can alter the value of assets and liabilities, impacting the accuracy of financial statements. Exchange rate volatility also adds complexity, particularly for companies operating in international markets. Inflation accounting and foreign currency translation become crucial to ensure that financial reports reflect the true economic condition. This study aims to analyze the challenges faced by auditors in an unstable economic environment and to explore methods that can be utilized to enhance the accuracy and relevance of financial statements.